Patient BBIs Monitoring System and Movement Analysis using Machine Learning Techniques and IoT - et. al., V. Kovendan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Wireless technology has been developed for different medical fields. The pulse monitoring system is used and in some private medical places only recorded and not utilized properly. However, accessing large medical equipment is inconvenient and expensive. In this, The proposed real-time heart rate monitoring system extract the heart beats measurements and that is stored and retrieved via Arduino microcontroller which connects the heart rate to the internet and sends results to the web server and notifies it to the specialist. Zero crossing in the resulting filter bank output signal represents heart rates that are extracted from BBI’s. The obtained heart rate is classified using the algorithm to denote the condition of the patient to notify it to specialist. Finally, the HRV features are calculated from the extracted BBI’s. If any risk found, it sends the emergency alert notification to the specialist. This system also monitors the patient activity in case of any emergency of patient using the IR sensor connected to the Arduino micro controller which alerts the controller or the specialist by a buzzer. The proposed framework isn't just utilized by the trained professional yet additionally by different clients (User agreeable). It offers speed and exactness in outcomes and with negligible expense. This technique is planned a Heart Rate Monitor System utilizing Arduino and Heartbeat Sensor. The exhibition results are contrasted and ECG signal addressed by oscilloscope and manual heartbeat estimation of heartbeat rate, which gives great arrangement.